Research on skeletal muscle impact injury using a new rat model from a bioimpact machine - Liu, Jun; Liao, Zhikang; Wang, Jingkun; Xiang, Hongyi; Zhu, Xiyan; Che, Xingping; Tang, Yuqian; Xie, Jingru; Mao, Chengyi; Zhao, Hui; Xiong, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction： Skeletal muscle impact injury occurs frequently during sports, falls, and road traffic accidents. The reported studies on skeletal muscle injury are difficult to determine the injury parameters. Therefore, we developed a new model of gastrocnemius impact injury in rats with a bio-impact machine, with which the experimental operation could be conducted in feasibility from the recorded parameters. Through this novel model, we study the skeletal muscle impact injury mechanisms by combing temporal and spatial variation. Methods: The gastrocnemius of anesthetized rats were injured by a small pneumatic-driven bio-impact machine, the moving speed, and impact force were determined, and the whole impact process was captured by a high-speed camera. We observed the general condition of rats and measured the changes in injured calf circumference, evaluating calf injuries using MRI, gait analysis system, and pathology at different times after injury. Results: The gastrocnemius was injured at an impact speed of 6.63±0.25 m/s and a peak force of 1556.80±110.79N. The gait analysis system showed that the footprint area of the RH limb decreased significantly on the 1st day, then increased. The calf circumference of the injured limb increased rapidly on 1st day post-injury, then decreased in the next few days. MRI showed edema of subcutaneous and gastrocnemius on the 1st day, the area of edema decreased over the following days. HE staining showed edema of cells, extensive hyperemia of blood vessels, and infiltration of inflammatory cells on the 1st day. Cell edema was alleviated day by day, but inflammatory cell infiltration was the most on the 3rd day. TEM showed that the sarcoplasmic reticulum was dilated on the 1st day, the mitochondrial vacuolation was obvious on the 2nd day, and the glycogen deposition was prominent on the 5th. Conclusion: Our experiment developed a new and effective experimental animal model which is feasible to operation; The injured area of gastrocnemius began to show “map-like” changes in the light microscope on the 3rd day. Meanwhile, gastrocnemius showed a trend of "edema-mitochondrial vacuolation-inflammatory cell aggregation" after impact injury.